1988
DOI: 10.1002/chin.198852327
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Antitumour Properties of Some Titanocene Chalcogenates.

Abstract: ChemInform Abstract The chalcogen-coordinated titanocene chalcogenates (I)-(III) are tested against fluid Ehrlich ascites tumor for antitumor properties. The best antitumor activity is observed for (Ia) and (Ib) followed by (II) and (IIIa). These results confirm that bis(η5cyclopentadienyl)Ti(IV) diacido complexes can be widely varied at the position of the acido ligands without loss of antitumor potency. The titanocene derivatives (Ib), (II), and (IIIa) are the first neutral mercapto and seleno titanocene der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The first lane on the left (lane 1 in Fig. 1 12 , lane 4, does not affect migration of the DNA species, suggesting that there is no interaction under these conditions (possibly due to poor aqueous solubility). Despite the focus on DNA as a target for cancer therapy, it is highly likely that this is not the only target in the molecular mechanism of drug activity, and alternative assays are used and new ones are being developed.…”
Section: Preliminary Biological Characterization Of Potential Organommentioning
confidence: 96%
See 1 more Smart Citation
“…The first lane on the left (lane 1 in Fig. 1 12 , lane 4, does not affect migration of the DNA species, suggesting that there is no interaction under these conditions (possibly due to poor aqueous solubility). Despite the focus on DNA as a target for cancer therapy, it is highly likely that this is not the only target in the molecular mechanism of drug activity, and alternative assays are used and new ones are being developed.…”
Section: Preliminary Biological Characterization Of Potential Organommentioning
confidence: 96%
“…Two of the leading innovators in the field, Fish and Jaouen, recently summarized the core subjects that make up the field of bioorganometallic chemistry in a review published in Organometallics; 1 and a previous review on bioorganometallic chemistry that highlighted the potential of the subject is given by Jaouen et al 2 Various bioorganometallic topics have been identified, including the synthesis of biologically relevant compounds via catalysis or organometallic intermediates, catalytic action on biomolecules, the synthesis of organometallic compounds with biologically relevant co-ligands, organometallic Bioorganometallic Chemistry 44 and a second compound, ferrocifen, which is a ferrocene derivative of tamoxifen, 19,45 looks set to enter clinical trials in the near future (Jaouen G, personal communication). Main-group organometallic complexes are not listed in Table 1, although some compounds such as diorganotin(IV) derivatives have been known to have antiproliferative activity on specific cancers for many years.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, the transport mechanism was found to be rather unspecific with regard to the choice of cells that incorporate the drug [13]. Due to the triumph of cisplatin on the one hand and its imperfections as a cancerostatic drug outlined on the other hand, an extensive research toward other coordination compounds was initiated, with mainly platinum as central metal ion but also encompassing complexes of ruthenium [14][15][16], titanium [14,17], gallium [18,19] …”
Section: State-of-the-art Of Anticancer Metallodrug Developmentmentioning
confidence: 99%
“…It can be easily derivatized and functionalized or oxidized to ferricenium salts . Many ferrocenyl compounds display considerable cytotoxic, antitumor, antimalarial, and antifungal activity . Potential applications of ferrocene derivatives as electrochemical sensors in the field of functional materials have attracted considerable attention in recent years .…”
Section: Introductionmentioning
confidence: 99%